2010
DOI: 10.1186/1741-7015-8-12
|View full text |Cite
|
Sign up to set email alerts
|

A functional polymorphism in the DNA methyltransferase-3A promoter modifies the susceptibility in gastric cancer but not in esophageal carcinoma

Abstract: BackgroundDNA-methyltransferase (DNMT)-3A plays an important role in the development of embryogenesis and the generation of aberrant methylation in carcinogenesis. The aim of this study was to investigate the role of a DNMT3A promoter genetic variant on its transcriptional activity and to evaluate the association between DNMT3A gene polymorphism and the susceptibility to gastric cancer (GC) and oesophagus carcinoma (EC) in the Chinese population.MethodsWe selected one of the single nucleotide polymorphisms (SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 35 publications
0
65
1
1
Order By: Relevance
“…Several studies have found that DNMT3a is over-expressed in human cancers, suggesting that it may be involved in tumorgenesis and tumor progression (Ding et al, 2008;He et al, 2011;Yang et al, 2011). Recently, DNMT3a SNPs rs1550117 and rs13420827 were also found to be significantly associated with GC (Fan et al, 2010;Wu et al, 2012;Yang et al, 2012). The aim of this study is to confirm the formerly reported association between the DNMT3a polymorphisms and GC in a large number of Chinese subjects, as well as to examine the association with H.pylori infection and GA.…”
Section: Dnmt3amentioning
confidence: 60%
See 4 more Smart Citations
“…Several studies have found that DNMT3a is over-expressed in human cancers, suggesting that it may be involved in tumorgenesis and tumor progression (Ding et al, 2008;He et al, 2011;Yang et al, 2011). Recently, DNMT3a SNPs rs1550117 and rs13420827 were also found to be significantly associated with GC (Fan et al, 2010;Wu et al, 2012;Yang et al, 2012). The aim of this study is to confirm the formerly reported association between the DNMT3a polymorphisms and GC in a large number of Chinese subjects, as well as to examine the association with H.pylori infection and GA.…”
Section: Dnmt3amentioning
confidence: 60%
“…MUC1 gene expression is regulated by DNA methylation, for instance, MUC1 mRNA expression in MUC1-negative cells was restored by the treatment with (Yamada et al, 2008). The luciferase assay demonstrated that the promoter activity of rs1550117 A allele of DNMT3a was significantly higher (more than two fold) than the G allele in Fan's study (Fan et al, 2010). Therefore, we can propose that DNMT3a rs1550117 GgA transition might increase the expression of DNMT3a and induce transcriptional repression of MUC1, resulting in the attenuation of MUC1 protective function.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations